Nutritional condition of children who benefit from the Bolsa Família programme in a city of northwestern São Paulo State, Brazil - dos Santos, Fabiana Pelegrin Cogo; De Vitta, Fabiana Cristina Frigieri [UNESP]; De Conti, Marta Helena Souza; Marta, Sara Nader; Gatti, Márcia Aparecida Nuevo; Simeão, Sandra Fiorelli de Almeida Penteado; De Vitta, Alberto (Faculdade de Filosofia e Ciências, 2015)
Introdution: The direct income transfer programmes such as BolsaFamília have the important function of making it possible for aspects of life to receive the necessary care and importance in order to improve the quality of life. One of the aspects concerns food and healthy nutrition. Objective: The objective was to assess the nutritional condition of children under five years old whose families are benefited by the programmeBolsaFamília in a city of northwestern São Paulo state, Brazil. Methods: A cross-sectional and retrospective study was carried out using the medical records of 284 children under the age of five, from which socio-demographic, weight and height data were collected. In order to diagnose children's nutritional condition,the indicators weight/age, height/age and weight/height were used, from the cutoffpoint z-score, recommended by the WHO Global Database on Child Growth and Malnutrition. Descriptive statistics and the Chi-square test were used to analyse data, assessing the association of indicators, gender and age. Results: 8.8% of the children have deficits concerning height/age and 4.2% have deficits concerning weight/age; 8.1% and 7.4% are overweight concerning weight/age and weight/height; 4.6 % of the children under 2 years oldhave higher weight than the expected for their age and also for their height, and 7.8% of the children have low height for their age. The prevalence of weight deficit and excess in children observed in this study were similar to those found in other regions of Brazil. Conclusion: The maintenance of the nutritional surveillance system is extremely important in order to detect risk groups and help plan effective measures to prevent and correct nutritional problems.
Keywords: Anthropometry; Children's health; Nutrition programmes and policies; Nutritional assessment